The Effect of Interaction of Personal Extraversion and Agreeableness on Work Engagement - Muhammad Rusdi; Rulitawati Rulitawati; Hilma Suryani (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
This research is a quantitative research that aims to determine the effect of extraversion personality interactions and agreeableness on the work involvement of lecturers at Raden Fatah State Islamic University Palembang, South Sumatra. The focus of this research is on the personality of the lecturer and aims to explore the influence of the interaction between extraversion and agreeableness on work involvement. The analytical method used is descriptive qualitative and quantitative analysis. The form of analysis of the validity of exploratory factor analysis and through the SPSS program, the results concludedit does not thatindicate that the interaction between extraversion and agreeableness has a positive and significant influence on work involvement. The results obtained by extraversion having an alpha of 0.945 extraversion have a significant effect on work involvement, while agreeableness has an alpha of 0.965, and work involvement has an alpha of 0.761. agreeableness has a significant effect on work involvement. Keywords - extraversion, agreeableness, work involvement